Pengetahuan Ibu Nifas Tentang Perawatan Payudara di Puskesmas Nusa Indah Kota Bengkulu - Depi Yupita; Sardaniah Sardaniah (KOLONI, 2023)
Breast care is one of the most important things to do in order tosmooth milk production and overcome problems that hinder the process of exclusive breastfeeding. One of the inhibiting factors that often occur is such as immersed nipples, little milk coming out, nipple blisters, swelling and pain in the breast. If not immediately overcome, these problems will get worse or more serious, resulting in babies not getting exclusively breastfed and meeting the nutritional needs of infants reduced. Thisstudy aims to determine the picture of postpartum mothers' knowledge about breast care in Nusa Indah Health Center, Bengkulu City using quantitative descriptive research methods. The population in this study was 102 people. Sampling in this study used purposive sampling techniques with a sample of 50 respondents. The data collection method uses questionnaires and uses univariate analysis. The results of research conducted on 50 respondents obtained that the picture of maternal knowledge of breast care is with good categories as much as (14%), sufficient categories as many as (76%) and less categories as much (10%). It is hoped that the puskesmas can increase the provision of health counseling on matters related to breast care problems. Keywords: Knowledge, Postpartum Mother, and Breast Care